The Influence of Work Discipline, Work Motivation, and Job Satisfaction on Employee Performance: Literature Review - Theodorus Kristianto (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The purpose of writing this article is to analyze the influence of work discipline, work motivation, and job satisfaction on employee performance in 10 articles. This literature review aims to identify and summarize previously published articles without any criticism of the articles to be reviewed. The type of research used in these 10 articles is quantitative research. Employees are people who are able to do their jobs, so employees as human resources for the company are very important to support the process of achieving the targets that have been set. The results of this study have found a positive relationship between variables. Among them, work discipline affects employee performance, work motivation affects employee performance, and job satisfaction affects employee performance. This study produced several studies from 10 articles that have provided scientific conclusions. The results of this study are expected to be a contribution that can provide convenience for other researchers who will develop scientific works with the same theme in the future.